Pengembangan Perangkat Pembelajaran Bercirikan Penemuan Terbimbing untuk Meningkatkan Kemampuan Penalaran Matematis Siswa pada Materi Barisan Aritmetika dan Geometri Kelas X - Izzatul Ulya; Ipung Yuwono; Abdul Qohar (Jurnal Kajian Pembelajaran Matematika, 2017)
This research is development research. Objective Research and development is to describe the process and results of development characterized guided discovery to students of class X are valid, practical and effective to improve students' mathematical reasoning. Expected product specification is characterized by the RPP and LKS guided discovery. This study uses Plomp  development model (2007) which consists of two stages: preliminary research (initial research) and prototyping (development stage). Based on the results of a small trial, showed that the developed learning tools valid criteria, practical, and effective. So,the product of development can be used as mathematic learning device in sequance and series, because   achieve valid, practical, and effective criteria.